Perbaikan Kualitas Kerja Dengan Desain Alat Penopang Kepala Bagi Buruh Suwun Di Pasar Badung Denpasar - I Made Bulda Mahayana (Jurnal Kesehatan Lingkungan (JKL), 2021)
Abstract : One side of industrialization have followed the progress of science and technology in the formal workers, informal workers the other hand very little attention from the government, such as suwun workers  lift transport of goods in the Market Badung, Denpasar. The purpose of research is to identify the workload and subjective complaints suwun workers before and after using the tool supporting head in the Market Badung, Denpasar. This type of research is pre experiment with the same study design subject of a pattern of "One Group Pretest-Posttest Design". Large sample of 14 persons. The results of the research work environment temperatures between 30-32⁰C; 80-87% humidity and wind speed ranges between 10-14 km/h. A decline in the average value of the pulse rate of 5.47% of the  workers suwun who use braces head with the tool supporting that do not use the head and there are differences in the pulse of work before and after using the tool supporting head (p 0.05). A decline in the average value of subjective complaints 11.43% suwun workers who use the tool supporting head with  do not use the the tool supporting head and there are differences in subjective complaints before and after using the tool supporting head (p 0.05). Conclusion No difference pulse work and subjective complaints suwun workers at Market Badung Denpasar before and after using the tool supporting head. Advice to the parties concerned to continue to disseminate to the workers suwun about the benefits derived from the use of tools supporting the head and the other researchers in order to create a more the tool supporting head inovasif and modern.  Keywords : the tool supporting head, workload, subjective complaints